The analyze of green space need in Surabaya City using Gerarkis Method for 2010–2020 - Rasendriya Ramanda Darettamarlan; Husnul Hidayat; Mohammad Rohmaneo Darminto; Danar Guruh Pratomo (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Surabaya City is the second-largest city based on the population in Indonesia that is affected by the development of urban planning in the city. The development of the urban areas affected the increase of socio-economic development and peri-urban demographics but often took over land or green open spaces. It is an unavoidable possibility of air pollution due to the imbalance between oxygen producers and existing oxygen users. It is necessary to calculate the prediction of green open space requirements using the Gerarkis Method, which predicts green open spaces based on oxygen demand by using the number of residents, motor vehicles, livestock, industrial factories, and hotels. With the Gerarkis Method, the prediction of the need for green open space in Surabaya City for 2010–2020 is 22,088.89 hectares to 31,950.84 with the increased majority value in the area, except in 2015 and 2020, due to decreased users. This method proves that the need for oxygen produced from plants is increasing, making Surabaya City needs more green open space to make Surabaya City livable.